2009
DOI: 10.1007/s10936-008-9097-8
|View full text |Cite
|
Sign up to set email alerts
|

Regional and Foreign Accent Processing in English: Can Listeners Adapt?

Abstract: Recent data suggest that the first presentation of a foreign accent triggers a delay in word identification, followed by a subsequent adaptation. This study examines under what conditions the delay resumes to baseline level. The delay will be experimentally induced by the presentation of sentences spoken to listeners in a foreign or a regional accent as part of a lexical decision task for words placed at the end of sentences. Using a blocked design of accents presentation, Experiment 1 shows that accent change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
119
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(126 citation statements)
references
References 24 publications
5
119
2
Order By: Relevance
“…In general, two languages overlap less in their phonology than two varieties of one language do. Floccia, Butler, Goslin, and Ellis (2009), for example, have argued that foreign accents tend to affect all phonemes, whereas dialects mainly affect vowels. With respect to perceived accentedness, regional accents are also judged to be more similar to the standard variety of a language than foreign accents are (Floccia, Goslin, Girard, & Konopcynski, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In general, two languages overlap less in their phonology than two varieties of one language do. Floccia, Butler, Goslin, and Ellis (2009), for example, have argued that foreign accents tend to affect all phonemes, whereas dialects mainly affect vowels. With respect to perceived accentedness, regional accents are also judged to be more similar to the standard variety of a language than foreign accents are (Floccia, Goslin, Girard, & Konopcynski, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, Floccia et al (2009) found that listeners' reaction times never recovered from the initial disruption caused by an accent switch. It is difficult to tease this issue apart by conducting further tests of this type away from a formal laboratory setting, but future research could manipulate the accent of the experimenter to see, for example, if a GE speaking experimenter would elicit different results.…”
Section: Role Of Long-term Familiaritymentioning
confidence: 95%
“…Nathan, Wells & Donlan, 1998;Nathan & Wells, 2001;Fraser Gupta 2005;Floccia, Goslin, Girard, & Konopczynski, 2006;Floccia, Butler, Goslin, & Ellis, 2009;Adank, Evans, Stuart-Smith, & Scott, 2009;Sumner & Samuel, 2009). The typical pattern is that speech in one's own accent is easier to understand than speech in a different regional accent, which in turn is easier to understand than non-native accented speech (Adank et al, 2009;Floccia et al, 2006; but see also Floccia et al, 2009). The processing costs associated with listening to other accents may arise because the acoustic-phonetic input from another accent produces either weak activation of intended words, and/or inappropriate activation of competitor words (Clopper, Pierrehumbert & Tamati, 2010;Dahan, Drucker & Scarborough, 2008).…”
Section: Variation In Speech: Idiolect and Accentmentioning
confidence: 99%
See 1 more Smart Citation
“…A great deal of recent research has shown that it is necessary to consider the differences and commonalities between bilinguals' and monolinguals' speech processing. Our study thus tests whether bilinguals' linguistic experience affects the way they adjust to regional accents, as it does in monolinguals (e.g., Conrey et al, 2005;Dufour et al, 2013;Floccia, Butler, Goslin, & Ellis, 2009;Floccia et al, 2006).…”
Section: Introductionmentioning
confidence: 99%